(untitled) - Molidor, John B. (Hoboken, New Jersey, 2012)
How acting a little crazy and thinking outside of the box can get you the job you want. Ever hear of a job candidate stretching out on the interviewer's floor to fill out an application? Or an applicant who sees nothing wrong with texting during the interview? Securing a job interview is a golden opportunity. The crazy-bad behavior described above will not net a job offer. Crazy Good Interviewing shows readers that crazy-good behavior, however, can make an applicant stand out favorably in a sea of mediocrity. Take the candidate who created a keynote presentation on his iPad to show what he could bring to the job or the one who created a DVD highlighting her abilities. Crazy Good Interviewing is a book geared toward those who are looking for work in this tough economy. Addresses how slightly eccentric behaviors can tip the scales in the applicant's favor Delves into how to access your three key strengths, how to use body language effectively, how to prepare a five-sentence history that builds a bridge to the interviewer, and more.Turn just plain crazy into crazy-good, and land the job at your next interview.
Keywords: Employment interviewing,Phỏng vấn tuyển dụng